I know sup(AB) = sup(A)sup(B) if A and B are nonnegative, but what if the assumption is dropped that A and B are nonnegative. Does this change the answer?

Printable View

- September 18th 2013, 10:30 AMmikewienermsup(AB) = sup(A)sup(B) Question
I know sup(AB) = sup(A)sup(B) if A and B are nonnegative, but what if the assumption is dropped that A and B are nonnegative. Does this change the answer?

- September 18th 2013, 10:58 AMPlatoRe: sup(AB) = sup(A)sup(B) Question
- September 18th 2013, 01:03 PMShakarriRe: sup(AB) = sup(A)sup(B) Question
Consider the case where A is the set [-10,5] and B is the set [-10,4]